Using a multi‐model ensemble approach to determine biodiversity hotspots with limited occurrence data in understudied areas: An example using freshwater mussels in México. Issue 5 (13th May 2022) - Kiser, Alexander H.; Cummings, Kevin S.; Tiemann, Jeremy S.; Smith, Chase H.; Johnson, Nathan A.; Lopez, Roel R.; Randklev, Charles R.
Abstract: Species distribution models (SDMs) are an increasingly important tool for conservation particularly for difficult‐to‐study locations and with understudied fauna. Our aims were to (1) use SDMs and ensemble SDMs to predict the distribution of freshwater mussels in the Pánuco River Basin in Central México; (2) determine habitat factors shaping freshwater mussel occurrence; and (3) use predicted occupancy across a range of taxa to identify freshwater mussel biodiversity hotspots to guide conservation and management. In the Pánuco River Basin, we modeled the distributions of 11 freshwater mussel species using an ensemble approach, wherein multiple SDM methodologies were combined to create a single ensemble map of predicted occupancy. A total of 621 species‐specific observations at 87 sites were used to create species‐specific ensembles. These predictive species ensembles were then combined to create local diversity hotspot maps. Precipitation during the warmest quarter, elevation, and mean temperature were consistently the most important discriminatory environmental variables among species, whereas land use had limited influence across all taxa. To the best of our knowledge, our study is the first freshwater mussel‐focused research to use an ensemble approach to determine species distribution and predict biodiversity hotspots. Our study can be used to guide not only current conservation efforts but also prioritize areas for future conservation and study. Abstract : This research article evaluates the utility of multi‐model ensemble species distribution models (ESDMs) to predict occupancy in regions where there is limited distribution and environmental data. Our study focuses on freshwater mussels, which are globally imperiled, in the Pánuco River Basin in central México, a region considered one of 25 biodiversity hotspots in the world. We identified climate and landscape factors that were helpful for explaining occupancy and should be useful for conservationists in this region interested in better understanding how climate change and flow contribute to mussel persistence.